A wearable vibrotactile system for distributed guidance in teleoperation and virtual environments. (February 2019) - Bai, Dongming; Ju, Feng; Qi, Fei; Cao, Yanfei; Wang, Yaoyao; Chen, Bai
A novel wearable vibrotactile system is proposed in this article to enhance the performance of teleoperation robot systems. Using a wearable vibrotactile glove, the proposed system guides the operator in the master–slave control through a vibrotactile-visual guidance method. Based on sensory substitution, the vibrotactile-visual combined guidance method combines vibration stimuli and visual feedback to substitute the virtual guidance force. A vibrotactile potential field is constructed in the workspace of the master-operator to calculate the frequency of the vibration stimulus. To provide vibration stimuli, a novel vibrotactile glove is designed and manufactured based on the layout of the sensitive region of human hand. As the human hand is unable to discriminate vibration stimuli of all frequencies, the vibration stimulus is discretization according to the result of the vibration discriminability experiment. At last, two contrast experiments in obstacle-free and obstacle-existing environments are conducted to verify the feasibility and effectiveness of the wearable vibrotactile system. The results show that this wearable vibrotactile system is an effective solution for guiding the operators in teleoperation and virtual environments.